Analysis of Productivity Growth and Technological Progress on Irrigated Wheat Crop in Provinces of South-West Region of Iran - Hassanpour, Behrooz; Karami, Ayat (Asian Journal of Biological and Life Sciences, 2017)
Wheat a staple food for humans is one the most important Iran's strategic agricultural products. Every year, more than 50% of the total cultivated area devoted to wheat crops. The objectives of study were to measure the growth of total factor productivity and then decomposed into its constituent factors, namely the growth of technical efficiency and technological change. The contribution of each factors in productivity growth in irrigated wheat farms provinces studied in the south-west region were compared. For this purpose, the method of Data Envelopment Analysis and the Malmquist index is used. Data input-output in cultivate wheat related to each of the provincial panel data during 12-year )2000-2011( from the Ministry of Agriculture, received and processed. The results showed that except Kohgiloyeh-va-Boyerahmad province, the provinces studied had growth in productivity. The greatest growth in productivity in wheat farms is concerned with an average 7.3% per year in the provinces of Fars and Khuzestan. Average annual productivity in the provinces of Ilam, Isfahan, Boushehr, Charmahal, and Kohgilouyeh as 3.1, 1.7, 1.1, 1, and -0.9 measured, respectively. Decomposition of productivity growth into its component factors in irrigated wheat fields showed that the major contribution to productivity growth, resulting from technological change )i.e., the application of modern technologies in the farms( and the change in technical efficiency )i.e., managing the use of inputs( in all provinces south-west region of the country is in recession. The investment to improve education and promotion programs appropriate for better management of the wheat fields is proposed.
Keywords: DEA; Malmquist index; Technical efficiency growth; Technological change; TFPG; Wheat